Model Groundwater (Sustainable Management) Bill, 2017: a new paradigm for groundwater regulation. Issue 3 (2nd September 2018) - Cullet, Philippe
ABSTRACT: The Groundwater (Sustainable Management) Bill, 2017 drafted by the Ministry of Water Resources, River Development & Ganga Rejuvenation provides a new template that states can use to adopt legislation capable of addressing the fast-increasing groundwater crisis faced by many states. This Bill follows on an earlier model bill drafted in 1970 and updated several times until 2005 on which the dozen of existing groundwater acts are based. This 1970 template is unsuited to the present needs of a country where groundwater is now the primary source of drinking water and irrigation. In particular, it fails to provide for local-level regulation of what is often known as the most local source of water and fails to provide for conservation measures at aquifer level. The 2017 Bill integrates legal developments having taking place since the 1970s, such as the decentralization reforms kick-started in the 1990s, the recognition of water as a fundamental right and its recognition as a public trust. In doing so, it provides new bases for regulating groundwater as a public resource and to take measures at aquifer level, something that is crucial to address ongoing overexploitation and falling water tables.